Aprofundando o estudo de sequências e progressões no ensino médio - Leal, Adriano Carlos (2017)
This work intends to deepen the study of sequences and progressions in the scope of High School. In order to do so, we introduce some advanced themes, such as induction, limits, convergence and divergence and show the connections with progressions, functions and interest rates. We also introduce other sequences, besides arithmetic and geometric progressions, and present a discussion about divergent series, subject that is little explored even in graduation courses. We finalize our work presenting some interesting problems that can be explored in the classroom.